Selective adsorption of ions in charged slit-systems - Valiskó, M.; Henderson, D.; Boda, D. (Condensed Matter Physics, 2013)
We study the selective adsorption of various cations into a layered slit system using grand canonical Monte Carlo simulations. The slit system is formed by a series of negatively charged membranes. The electrolyte contains two kinds of cations with different sizes and valences modeled by charged hard spheres immersed in a continuum dielectric solvent. We present results for various cases depending on the combinations of the properties of the competing cations. We concentrate to the case when the divalent cations are larger than the monovalent cations. In this case, size and charge have counterbalancing effects, which results in interesting selectivity phenomena. Ми дослiджуємо селективну адсорбцiю рiзних катiонiв у шарувату щiлиноподiбну систему, використовуючи Монте Карло симуляцiї у великому канонiчному ансамблi. Щiлиноподiбна система формується послiдовнiстю негативно заряджених мембран. Електролiт мiстить два типи катiонiв рiзних розмiрiв i валентностей, якi моделюються зарядженими твердими сферами, зануреними в однорiдний дiелектричний розчинник. Ми представляємо результати для рiзних випадкiв в залежностi вiд комбiнацiї властивостей конкуруючих катiонiв. Ми розглядаємо випадок, коли двовалентнi катiони є бiльшi, нiж моновалентнi. У цьому випадку, розмiр i заряд мають зрiвноважувальний ефект, що приводить до цiкавих селективних явищ.